2023
DOI: 10.3389/fmicb.2023.1130170
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of Shiga toxin-producing Escherichia coli strains recovered from bovine carcasses in Uruguay

Abstract: IntroductionShiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen that cause food-borne diseases in humans. Cattle and derived foodstuffs play a known role as reservoir and vehicles, respectively. In Uruguay, information about the characteristics of circulating STEC in meat productive chain is scarce. The aim was to characterize STEC strains recovered from 800 bovine carcasses of different slaughterhouses.MethodsTo characterize STEC strains we use classical microbiological procedures, Whole Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This difference could reflect the extensive use of antimicrobials in dairy herds to treat infectious diseases such as NCD, particularly in animals with a high risk of dying. Additionally, recent work carried out in isolates from different sources including human samples and children’s feces, beef and carcasses in our country did not identify a high level of antimicrobial resistance in STEC [ 46 , 47 ]. In our work, antimicrobial resistance and even multi-resistance seems alarming.…”
Section: Discussionmentioning
confidence: 73%
“…This difference could reflect the extensive use of antimicrobials in dairy herds to treat infectious diseases such as NCD, particularly in animals with a high risk of dying. Additionally, recent work carried out in isolates from different sources including human samples and children’s feces, beef and carcasses in our country did not identify a high level of antimicrobial resistance in STEC [ 46 , 47 ]. In our work, antimicrobial resistance and even multi-resistance seems alarming.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that 6–25% of patients infected with STEC develop HUS, and the rate is higher in children [ 2 , 3 , 4 ]. More than 1000 different serotypes of STEC have been defined in humans, animals and the environment [ 5 , 6 , 7 ]. O157:H7 is the predominant serotype causing more severe disease.…”
Section: Introductionmentioning
confidence: 99%